The Value of Serum NR2 Antibody in Prediction of Post-Cardiopulmonary Resuscitation Survival - Ali Bidari; Samira Vaziri; Ehsan Moazen Zadeh; Sahar Farahmand; Elham Talachian (Archives of Academic Emergency Medicine, 2018)
Introduction: N-methyl-D-aspartate receptor subunits antibody (NR2-ab) is a sensitive marker of ischemic brain damage in clinical circumstances, such as cerebrovascular accidents. We aimed to assess the value of serum NR2-ab in predicting the post-cardiopulmonary resuscitation (CPR) survival. Methods: In this cohort study, we examined serum NR2-ab levels 1 hour after the return of spontaneous circulation (ROSC) in 49 successfully resuscitated patients. Patients with traumatic or asphyxic arrests, prior neurological insults, or major medical illnesses were excluded. Participants were followed until death or hospital discharge. Demographic data, coronary artery disease risk factors, time before initiation of CPR, and CPR duration were documented.  In addition, Glasgow coma scale (GCS), blood pressure, and survival status of patients were recorded at 1, 6, 24, and 72 hour(s) after ROSC. Descriptive analyses were performed, and the Cox proportional hazard model was applied to assess if NR2-ab level is an independent predictive factor of survival. Results: 49 successfully resuscitated patients were evaluated; 27 (55%) survived to hospital discharge, 4 (8.1%) were in vegetative state, 10 (20.4%) were physically disabled, and 13 (26.5%) were physically functional. Within 72 hours of ROSC all of the 12 NR2-ab positive patients died. In contrast, 31 (84%) of the NR2-ab negative patients survived. Sensitivity, specificity, positive and negative likelihood ratios of NR2-ab in prediction of survival were 54.5% (95%CI=32.7%-74.9%), 100% (95%CI=84.5%-100%), infinite, and 45.5% (95%CI=28.8%-71.8%), respectively. Subsequent analysis showed that both NR2-ab status and GCS were independent risk factors of death. Conclusions: A positive NR2-ab serum test 1 hour after ROSC correlated with lower 72-hour survival. Further studies are required to validate this finding and demonstrate the value of a quantitative NR2-ab assay and its optimal time of measurement.